Effects of Drying Methods on Physicochemical and Rheological Properties of Porcine Plasma Protein - Samsalee, Namfon; Sothornvit, Rungsinee (Agriculture and Natural Resources, 2014)
Porcine plasma is an important source of high protein content which can be used for food products. The objective of this study was to determine the effect of drying methods on the properties of porcine plasma protein powder (PPP). The effects of freeze drying, and spray drying at two levels of inlet air temperature (140 and 200 oC) were studied on the physicochemical and rheological properties of PPP. It was found that freeze-dried PPP showed signiﬁ cantly (P < 0.05) higher solubility and oil binding capacity (OBC) than spray-dried PPP. The higher inlet air temperature provided slightly higher OBC and water holding capacity of PPP. Moreover freeze-dried PPP had a red-yellow color as indicated by the lower values for lightness (L*), higher redness (a*) and higher yellowness (b*), compared with spraydried PPP which was green-yellow in color. As expected, the lower inlet temperature with spray drying exhibited higher values for L*, a* and b* of PPP. All dried PPP showed a typical non-Newtonian ﬂ ow behavior. Freeze-dried PPP exhibited Bingham plastic ﬂ uid behavior while spray-dried PPP exhibited pseudoplastic ﬂ uid behavior. Therefore, the drying method affected different PPP properties which can be tailored to food processing and application to improve food quality.